Discrete-time control system analysis and design - Leondes, Cornelius T. (Control and dynamic systems, 1995)
Praise for Previous Volumes "This book will be a useful reference to control engineers and researchers. The papers contained cover well the recent advances in the field of modern control theory."--IEEE GROUP CORRESPONDENCE "This book will help all those researchers who valiantly try to keep abreast of what is new in the theory and practice of optimal control."--CONTROL